Quality Control Analysis to Reduce Rejects in Plastic Seal Manufacturing - Siddik, Khairul; Nugroho, Rosalendro Eddy (International Journal of Indonesian Business Review, 2025)
Purpose – This study aims to identify the root causes of product rejects and evaluate the effectiveness of quality control improvements at PT Karya Gemilang Indonusa, a plastic seal manufacturing company. Methodology – The methodology used includes Statistical Process Control (SPC), especially p-chart to monitor defect proportion, and Fishbone Diagram for root cause analysis. Data were collected from production reports between January and December 2024 and after improvements in January–April 2025. Findings – The study revealed that flashing and short mold are the dominant defects, accounting for more than 55% of total rejects. After corrective actions such as operator training, machine maintenance, and parameter adjustments, the reject rate reduced from 12.91% to 4.48%, and the process capability index (Cpk) improved from 0.333 to 0.667. Novelty – The integration of SPC and Fishbone Diagram in a real-world manufacturing setting effectively reduced rejects and increased process stability, supporting sustainable production.